Association of Statins With Decreased Acute Pancreatitis Severity: A Propensity Score Analysis. Issue 8 (September 2018) - Lee, Peter J.; Modha, Kunjam; Chua, Tiffany; Chak, Amitabh; Jang, Daniel; Lopez, Rocio; Gougol, Amir; Papachristou, Georgios I.; Stevens, Tyler
Abstract : Background: Statins possess anti-inflammatory properties and have a protective effect in certain inflammatory conditions; however, their effect on the natural history of pancreatitis is unknown. Aim: The aim of this study is to assess the effect of statin exposure on the severity of pancreatitis and incidence of organ failure using a propensity-matched approach. Methods: A historical cohort study was conducted of adult patients with acute pancreatitis (AP) admitted in the Cleveland Clinic Health System between 2007 and 2014. All medication, clinical, and outcomes data were extracted from the electronic medical record. Factors that influence statin use were included in a propensity model to minimize selection bias. Patients on and off statins were matched (1:1) based on the propensity score to simulate a randomized controlled trial. Measured outcomes included pancreatitis severity (Revised Atlanta Classification), incidence of multisystem organ failure (MSOF), new MSOF, acute necrosis, and death. Additional surrogate markers of severity included hospital length of stay, Bedside Index of Severity of Acute Pancreatitis (BISAP), and presence of SIRS. Results: A total of 110 subjects taking a statin at admission were matched with 210 subjects not on a statin. Known baseline factors that may influence statin use and severity of pancreatitis were evenly matched between the 2 groups. Patients on a statin were less likely to develop MSOF, severe AP and necrosis. Although less in-hospital death occurred in the statin group when compared to nonusers, the difference was not statistically significant (2% vs. 4%; P =0.38). Conclusions: Statin use is associated with decreased severity of AP observed as reduction in both overall MSOF incidence and new MSOF. Prospective randomized controlled trials are needed to determine the efficacy of statin drugs in the treatment of AP. Abstract : Supplemental Digital Content is available in the text.